Analisis Persepsi Mahasiswa Jurusan Akuntansi terhadap Profesi Akuntan Publik (Studi Kasus pada Mahasiswa Jurusan Akuntansi Universitas Internasional Jakarta Sebelum dan Sesudah Menempuh Mata Kuliah Auditing) - Bachtiar, Revioliyta (Universitas Nahdlatul Ulama Surabaya, 2025)
This study analyzes the extent to which the Auditing course changes the perceptions of Accounting students at Jakarta International University regarding the profession of Public Accountant before and after studying the course. The method used in this study uses a qualitative approach with in-depth interviews. The results show that before taking the Auditing course, students had a limited and often erroneous understanding of the profession of Public Accountant. After completing the Auditing course, there was a significant increase in understanding. Students began to understand the roles, duties, and responsibilities of an auditor. The main factors influencing this change include the case study-based learning method, the involvement of lecturers with professional experience, and an analytical approach in evaluating financial statements. Furthermore, the Auditing course also increased students' interest in the profession of public accountant, although some students still chose other career paths. These findings emphasize the importance of formal education in shaping students' understanding and interest in the profession of public accountant.